Institutional reorganisation can be inspired by forward-looking information systems. Issue 2 (23rd June 2014) - Ahamer, Gilbert; Mayer, Johannes
Abstract : Purpose: – This paper is the continuation of an earlier paper in this journal on global megatrends provoking institutional changes. It contains sectoral analyses with relevance to environmental protection. Conclusions for suitable institutional reorganisation of (environmental or other) institutions are presented. The paper aims to discuss these issues. Design/methodology/approach: – A planet-wide information system might optimally also include areas such as human development indicators, water supply and demand and deforestation issues. Findings: – While administrations are increasingly oriented towards servicing a society, environmental institutions should specifically take care of global megatrends in the following areas: genetic engineering and biological safety, integrated plant technology in industry, climate protection, agriculture, noise, emissions and air pollution, sustainability, spatial planning and regional planning, radiation protection and nuclear power, Environmental Impact Assessment (EIA) and Environmental Information Act, traffic, forest, water. Originality/value: – The approach of this paper is the long-term matching of (national) administrative structures with (global) megatrends.